DETERMINATION OF PESTICIDES IN RIVER SURFACE WATERS OF CENTRAL CHILE USING SPE-GC-MS MULTI-RESIDUE METHOD - Climent, María José; Sánchez-Martín, María Jesús; Rodríguez-Cruz, María Sonia; Pedreros, Pablo; Urrutia, Roberto; Herrero-Hernández, Eliseo (Journal of the Chilean Chemical Society, 2018)
In areas with agricultural activity, the excessive use of pesticides can contaminate water resources. That is why a multi-residue method based on solid-phase extraction (SPE) and gas chromatography analysis coupled to mass spectrometry (GS-MS) was used to determine eleven pesticides and five degradation products in surface water of Central Chile. The parameters that can affect the efficiency of the SPE process were optimized considering the information available in bibliography. As in other studies, the best results were obtained when 500 mL of water was pre-concentrated using Oasis HLB polymer cartridges and acetone and acetonitrile were used as solvents for the elution. To ensure good quantification, matrix-matched standards were used, providing good linearity in the studied concentration range (0.10-1.5 μg L-1), with recovery percentages > 60%, precisions < 19% and quantification limits < 0.1 μg L-1. The surface water samples were collected at the end of summer and winter seasons, considering rivers, creeks and irrigation canals of Cachapoal River basin. A percentage > 87% of the pesticides analyzed in this research were detected in more than one sampled site in both seasons. The most ubiquitous compounds were desethylterbuthylazine (DET), pyrimethanil, cyprodinil and diazinon, and the compounds detected in highest concentration were simazine and degradation products derived from triazines. Las Cabras and Tahuilla irrigation canals presented the highest concentrations of pesticides. Significant differences were found in the total concentration of pesticides for sites sampled at the end of the summer and winter season.